부정경쟁방지법상 트레이드 드레스 보호제도 고찰-중국과 한국의 보호법제 비교를 중심으로 - 정일남; Jung Ilnam (지식재산연구, 2017)
중국과 한국은 트레이드 드레스를 상표법상 입체상표제도와 부정경쟁방지법에 의해 보호하고 있다. 그중 양국의 부정경쟁방지법을 대상으로 트레이드 드레스의 보호요건을 비교·검토하고, 우리나라 보호규정이 트레이드 드레스를 전면적으로 보호할 수 있는지 보호대상의 관점에서 고찰하였다. 중국의 트레이드 드레스 보호규정인 반부정당경쟁법 제2조와 제5조 제2항은 우리나라 부정경쟁방지법 제2조 제1호 (차)목, (가)목과 유사하지만, 중국 학설과 판례가 일반조항으로 보고 있는 제2조는 일반조항이라고 보기에는 무리가 있으며, 개별조항인 중국의 제5조 제2항은 우리나라의 (가)목과 주지성을 요하는 대상과 보호범위, 기능성 관련 규정 유무에서 차이가 있다. 중국은 우리나라 부정경쟁방지법 제2조 제1호 (자)목과 같은 ‘상품형태의 모방금지’ 규정이 없어 트레이드 드레스 보호에 미흡한 면이 있다. 우리나라의 트레이드 드레스 보호는, 상품형태 등을 보호하는 (가)목·(자)목과 보충적 일반조항의 형태로 보호하는 (차)목으로 나뉘어 이분법적인 보호를 하고 있다. 따라서 부정경쟁방지법 내에서 트레이드 드레스의 출처에 대한 오인·혼동이 발생하는 것을 부정경쟁행위의 한 유형으로 규정하는 등 이를 명문화하여 법적 안정성을 도모하는 것이 필요하다. China and Korea protect trade dress under Trademark Act and Unfair Competition Prevention Act. Specifically, this paper is to study and compare detail provisions of protecting trade dress under Unfair Competition Prevention Act in China and Korea, and review whether Korea’s Unfair Competition Prevention Act provides complete protection to trade dress from the point of subject matter. Article 2 and 5(2) of China’s Unfair Competition Prevention Act are similar to Article 2(1)(j) and (a) of Korea’s Unfair Competition Prevention Act, however, there are differences, for example, in the scope of protection for famous marks and the presence of provisions relating to functionality between the two Acts. Further, there are no such provisions in China’s Unfair Competition Prevention Act as prohibiting copies of goods’ shape in Article 2(1)(i) of Korea’s Unfair Competition Prevention Act. To sum up, the subject matter of Korea’s Unfair Competition Prevention Act is binary structure, that is, protection of goods’ shape is provided under Article 2(1)(a) and (i), while others are protected under Article 2(1)(j). Therefore, it is suggested to stipulate misleading and/or confusion to sources of trade dress as a kind of unfair competitions under Korea’s Unfair Competition Prevention Act in order to promote legal stability.